2017
DOI: 10.3389/fncom.2017.00001
|View full text |Cite
|
Sign up to set email alerts
|

A Phase-Locking Analysis of Neuronal Firing Rhythms with Transcranial Magneto-Acoustical Stimulation Based on the Hodgkin-Huxley Neuron Model

Abstract: Transcranial magneto-acoustical stimulation (TMAS) uses ultrasonic waves and a static magnetic field to generate electric current in nerve tissues for the purpose of modulating neuronal activities. It has the advantage of high spatial resolution and penetration depth. Neuronal firing rhythms carry and transmit nerve information in neural systems. In this study, we investigated the phase-locking characteristics of neuronal firing rhythms with TMAS based on the Hodgkin-Huxley neuron model. The simulation results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 17 publications
0
27
0
Order By: Relevance
“…It should be noted that one possible issue with connectionist models is that several modelling choices, such as the format of the input and output representations [ 85 ] or the particular choice of learning algorithm [ 86 ], may have a crucial impact on the model's behaviour. One strength of the simulations presented in this article is that we made virtually no assumptions about the input/output representation format (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that one possible issue with connectionist models is that several modelling choices, such as the format of the input and output representations [ 85 ] or the particular choice of learning algorithm [ 86 ], may have a crucial impact on the model's behaviour. One strength of the simulations presented in this article is that we made virtually no assumptions about the input/output representation format (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…For excitatory connections, it has been shown that slow firing rate variations can also be achieved with overlapping clusters (Litwin-Kumar and Doiron 2012 ), mutually connected weight hub units with strong inward synapses (Setareh et al. 2017 ) or a range of other connectivity types (Doiron and Litwin-Kumar 2014 ). Although the exact implementation may vary, we believe that our proposal of local balancing of structured networks provides a very robust solution for metastability.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of within-muscle coherence at task failure using motor unit spike trains decoded from the electromyographic signals has been reported to increase in muscles of both the upper and lower limbs [ 7 , 8 ] due to an intensification of the cortical demand associated with maintaining task stability during fatigue. Also recently, Reyes and colleagues [ 58 ] have reported a diminished beta (15–30 Hz) band intermuscular and corticomuscular coherence contributions in two synergistic hand muscles during a spring compression task, suggesting a disengagement of the two muscles at the level of motor cortex when the force becomes highly unstable. These results are comparable with ours as also in our task there is an inherent instability induced progressively by the approaching of voluntary exhaustion.…”
Section: Discussionmentioning
confidence: 99%